2015
DOI: 10.1073/pnas.1422225112
|View full text |Cite
|
Sign up to set email alerts
|

Meteorite-catalyzed syntheses of nucleosides and of other prebiotic compounds from formamide under proton irradiation

Abstract: Liquid formamide has been irradiated by high-energy proton beams in the presence of powdered meteorites, and the products of the catalyzed resulting syntheses were analyzed by mass spectrometry. Relative to the controls (no radiation, or no formamide, or no catalyst), an extremely rich, variegate, and prebiotically relevant panel of compounds was observed. The meteorites tested were representative of the four major classes: iron, stony iron, chondrites, and achondrites. The products obtained were amino acids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
157
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 123 publications
0
157
0
4
Order By: Relevance
“…Among such small organic molecules, formamide is assuming an ever more central role in prebiotic chemistry research, as recently shown in experiments mimicking some of those origins of life scenarios, such as laser sparks (6), UV light (7), proton irradiation (8), or shock waves (as in meteorite impacts) (9). The main reason for such strong interest in formamide, besides its ubiquitousness in the solar system, is its chemical flexibility: it can be formed from (or, conversely, dissociated into) different molecular species that represent fundamental building blocks, including H 2 , H 2 O, NH 3 , CO, HCN, HNCO, and HCOOH (10,11).…”
mentioning
confidence: 99%
“…Among such small organic molecules, formamide is assuming an ever more central role in prebiotic chemistry research, as recently shown in experiments mimicking some of those origins of life scenarios, such as laser sparks (6), UV light (7), proton irradiation (8), or shock waves (as in meteorite impacts) (9). The main reason for such strong interest in formamide, besides its ubiquitousness in the solar system, is its chemical flexibility: it can be formed from (or, conversely, dissociated into) different molecular species that represent fundamental building blocks, including H 2 , H 2 O, NH 3 , CO, HCN, HNCO, and HCOOH (10,11).…”
mentioning
confidence: 99%
“…51 At around 430K in liquid formamide most of the prebiotic building blocks (i.e. nucleobases, nucleosides) can be synthesized, 7,8,[52][53][54] and, after phosphorylation (Ref. 5 ), they can accumulate in the form of nucleotides.…”
Section: Prebiotic Implicationsmentioning
confidence: 99%
“…1,2 Their strained intramolecular phosphodiester linkage accumulates chemical energy which can be utilized to drive transphosphorylation reactions leading to oligonucleotides. 3 Recently, various plausible prebiotic pathways have been elaborated for their synthesis, [4][5][6] among which the one based on formamide 5,7,8 has been found to yield a mixture of both 2',3' and 3',5'-linked cyclic forms. Based on these experimental results it has been suggested that higher temperatures of the prebiotic environment favor accumulation of the 3',5' form over the 2',3' variant.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously these premises do not exclude the prebiotic formation of similar structures in either watery environments or gas-rich atmospheres, even though the chemistry of dust grains and interstellar bodies seems to be largely dominated by surface and solid state reactions (Williams and Viti 2013). Furthermore, as reported recently, meteoritic samples (presumably containing tiny amounts of organics) can also catalyze the formation of numerous prebiotic molecules and analogs by irradiation with high-energy protons of formamide serving as versatile scaffold (Saladino et al 2015). …”
Section: Introductionmentioning
confidence: 99%